La obra del compositor Manuel de Jesús Lozano y su contribución al patrimonio musical lojano y del país. Edición y difusión de su repertorio pianístico producido en el periodo 1928-1990. - Remache Alasiche, Segundo Fabián (2022)
Loja's musical heritage is made up of the musical productions developed by various composers, most of whom have not been the object of study for possible investigations. Such is the case of Manuel de Jesús Lozano who has a considerable number of works written in various musical genres. In the present investigative work, it was proposed to carry out a process of the critical edition of those works that belong to the piano repertoire of the composer under study, which is located in the Salvador Zaragocín Tapia music museum in the city of Loja. For the scope of this project, the general objective was to edit and disseminate the piano repertoire of the composer Manuel de Jesús Lozano as a contribution to the development of the musical heritage of Loja and the country, for which an archive work was carried out that served to identify the number total number of works of the person being studied and select those that belong to his piano repertoire. In addition, we worked with a population of nineteen people, including a direct relative of the composer, to who an interview was applied to corroborate data necessary for the development of the investigation. The remaining eighteen people were pedagogues-pianists, who, through a survey, provided information about the reality and the interest of the Loja community in the composer's work. Likewise, they agree that the composer's repertoire has not been disseminated, therefore, it is necessary to develop this type of investigative work in which composers from Loja and Ecuador are taken into consideration. Within the conclusions that were determined through the development of this research, it has that the work of Manuel de Jesús Lozano is extensive and, however, mostly unknown. The edition and dissemination of the classified work will allow its interpretation and value of it. It is recommended to use the booklet included as an annex in this work, in which the edited works of the composer are presented along with his critical apparatus in order to keep Loja's musical heritage alive. Keyboards: music heritage, lojan music, Manuel de Jesús Lozano.